(9)(7)-(5)(-2)=

Simple and best practice solution for (9)(7)-(5)(-2)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (9)(7)-(5)(-2)= equation:


Simplifying
(9)(7) + -1(5)(-2) = 0

Multiply 9 * 7
63 + -1(5)(-2) = 0

Multiply -1 * 5
63 + -5 * -2 = 0

Multiply -5 * -2
63 + 10 = 0

Combine like terms: 63 + 10 = 73
73 = 0

Solving
73 = 0

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 3-2n=11 | | 7-(-1-4)= | | 8+3x=18+4x | | -2-4+7+3(-4)+17= | | 4-9x=26+2x | | 2(3x+4)=42 | | 5(x-2)+4=-11 | | 6+4(-4)= | | t^3-9t=0 | | 12h-10=42 | | 4(2x+3)=46 | | (3x+5)=3 | | (2x-5)(x+3)=(x-2)(2x+1) | | 12+(h+10)=42 | | 5(x+4)-x=0 | | 7+2x=5-4x | | (-2)[9+(-5)]= | | 3x+4=8-(6x-9) | | 7-5(5-7x)=0 | | (-2)(4)+5[6-(-2)]= | | 28=0.5*0.8*r^2 | | 5a-3(a+1)=-5 | | 16=0.5x | | 3w-10w-3+2=20 | | 47=7x+6(-1x+6) | | -48=4x+3(-4x+8) | | 74=3x+2(6x-8) | | 81=-2x-3(5x+7) | | x^2-36a^2+20x+100=0 | | -110=-2x+7(3x+6) | | 3(2x-1)-2=2(x+9)+1 | | x^2-16y^3=0 |

Equations solver categories